2019
DOI: 10.1049/iet-its.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Long automated driving phase affects take‐over performance

Abstract: We investigated the impact of automated driving phases of different durations (long vs. short) on take-over performance and driver state. Thirty participants drove on a dynamic simulator under autonomous mode for three successive periods of automated driving: a short (10 min), a long (1 hour) and another short (10 min) period, each ending with a take-over request. They performed a non-driving task, watching a film of their choice, throughout the autonomous phases. Driving performance -reaction time and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…The results also suggest that the OOTL phenomenon took some time to appear and that it increased with the duration of automated driving (Körber et al, 2015;Feldhütter et al, 2017;Bourrelly et al, 2019).…”
Section: What Constitutes Good Monitoring Of a Driving Situation?mentioning
confidence: 67%
See 1 more Smart Citation
“…The results also suggest that the OOTL phenomenon took some time to appear and that it increased with the duration of automated driving (Körber et al, 2015;Feldhütter et al, 2017;Bourrelly et al, 2019).…”
Section: What Constitutes Good Monitoring Of a Driving Situation?mentioning
confidence: 67%
“…In the aviation field, Molloy and Parasuraman (1996) showed that monitoring performance decreased with time. In the automated driving context, some studies have indicated that prolonged periods of automated driving rendered drivers further OOTL (Körber et al, 2015;Feldhütter et al, 2017;Bourrelly et al, 2019). For example, Bourelly et al (2019) observed longer reaction times (+0.5 s) to a critical event after 1 h of automated driving, compared to reactions to the same event after 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…Obvious limitations are that the task was only carried out in a simulator, so correspondence to real world behavior remains open, and that the task only lasted for a relatively short amount of time, so effects of learning or boredom remain uncertain. Future experiments are also required to better describe the automation supervision processes, in particular to describe how automation is impacting visual sequences over longer periods of time 65 . Investigations of visual sequences engaged in other driving scenarios would also be of interest.…”
Section: Discussion (Part Ii)mentioning
confidence: 99%
“…A period of automated driving may lead to a reduced driving performance compared to manual driving [7], [11], [12]. In addition, some evidence exists on that automation duration (i.e., the time drivers are exposed to automation) also reduces driving performance after a TOR [13], [14]. That is, longer automation duration seems to result in more degraded performance (e.g., longer response times, greater number of uncontrolled maneuvers, greater accelerations) than shorter automation duration [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some evidence exists on that automation duration (i.e., the time drivers are exposed to automation) also reduces driving performance after a TOR [13], [14]. That is, longer automation duration seems to result in more degraded performance (e.g., longer response times, greater number of uncontrolled maneuvers, greater accelerations) than shorter automation duration [13], [14]. However, at least one study showed no effects of automation duration on driving performance [15].…”
Section: Introductionmentioning
confidence: 99%